Papillary ependymoma with unique superficial cortical location: immunohistochemical and ultrastructural studies. A case report - Grajkowska, Wiesława; Matyja, Ewa; Pronicki, Maciej; Daszkiewicz, Paweł; Roszkowski, Marcin; Perek, Danuta; Drogosiewicz, Monika (Folia Neuropathologica, 2009)
Ependymomas are relatively rare neoplasms of the central nervous system that typically develop along cerebral ventricles and central canal of spinal cord. Occasionally, the tumours of ependymal origin arise supratentorially in brain parenchyma as ectopic cortical mass without any connection to the ventricular system. Ependymomas are heterogeneous group of tumours including cellular, papillary, clear cell and tanacytic histology. The papillary ependymoma is an unusual variant of ependymoma characterized by distinct morphology resembling other papillary tumours and corresponding to WHO grade II malignancy. We present an unique case of ependymoma with distinctive papillary morphology at ectopic superficial cortical localization. The tumour occurred in eleven-years-old girl as a large, well-circumscribed mass in the left parietal lobe without continuity with the ventricular system. The patient presented with severe headache, vomiting and sudden-onset right hemiparesis. Histopathologically, the tumour revealed distinct papillary pattern with numerous pseudorosettes. Immunohistochemically, the neoplastic cells of both papillary structures and pseudorosettes were positive for glial fibrillary acidic protein and vimentin, whereas they were only slightly immunoreactive for epithelial membrane antigen and negative for cytokeratins. Ultrastructural findings revealed the presence of cilia usually located in the neoplastic cell bodies and intermediate glial-like filaments. The final diagnosis of papillary ependymoma at ectopic superficial localization was based on both, immunophenotypic profile and ultrastructural features that confirmed ependymal nature of neoplastic cells.